2017
DOI: 10.1039/c6ra27485d
|View full text |Cite
|
Sign up to set email alerts
|

Importance of volatile AAEM species to char reactivity during volatile–char interactions

Abstract: Behaviour characteristics of volatile AAEM species during volatile–char interactions is important to promote char reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The formation and distribution of AAEMs (e.g., Ca), together with tar in the pore structure of graphite, reflect the important role of AAEM species in the homogeneous transformation of tar [35]. In addition, during heterogeneous reforming, AAEMs are precipitated together with volatile matter from corn straw, which will adhere/bond to the surface of the char-based catalyst [43] and participate in the heterogeneous reforming reaction of biomass tar. After tar reforming, the graphite surface contains a small amount of O, which is consistent with the result of Raman analysis.…”
Section: Reactivities Of Char-based Catalystsmentioning
confidence: 99%
“…The formation and distribution of AAEMs (e.g., Ca), together with tar in the pore structure of graphite, reflect the important role of AAEM species in the homogeneous transformation of tar [35]. In addition, during heterogeneous reforming, AAEMs are precipitated together with volatile matter from corn straw, which will adhere/bond to the surface of the char-based catalyst [43] and participate in the heterogeneous reforming reaction of biomass tar. After tar reforming, the graphite surface contains a small amount of O, which is consistent with the result of Raman analysis.…”
Section: Reactivities Of Char-based Catalystsmentioning
confidence: 99%
“…Samples taken the following tar reforming in (A) Ar over pyrolysis biochar, (B) Ar over H 2 O-activated biochar, and (C) Ar over CO 2activated biochar showed that the H 2 O/CO 2 activation of biochar played an important role in maintaining the biochar's active sites, such as surface O-containing functional groups and AAEM species (especially K and Ca) and improved its tar-reforming performance. According to Du et al [67], XPS revealed the evolution of AAEM species and char structures, and concentrations of AAEM species agreed well with surface atomic O concentrations. Similar results were obtained in Figure 10, where Ar reforming over H 2 O-activated biochar yielded a biochar with a higher surface content of O (16.25 atomic%), K (0.80 atomic%), and Ca (0.45 atomic%) than the samples from Ar reforming with the CO 2 -activated biochar and the pyrolysis biochar.…”
Section: Xps Analysis Of Biochar During Biomass Tar Reformingmentioning
confidence: 74%
“…The formation and distribution of AAEMs (e.g., Ca), together with tar in the pore structure of graphite, reflect the important role of AAEM species in the homogeneous transformation of tar [35]. In addition, during heterogeneous reforming, AAEMs are precipitated together with volatile matter from corn straw, which will adhere/bond to the surface of the char-based catalyst [43] and www.videleaf.com participate in the heterogeneous reforming reaction of biomass tar. After tar reforming, the graphite surface contains a small amount of O, which is consistent with the result of Raman analysis.…”
Section: Physical Structures Of Char-based Catalystsmentioning
confidence: 99%